Penerapan Nilai–Nilai Akhlak Dalam Kitab Bidayatul Hidayah - Nor Habibah; Muhammad Efendi; Siti Cholifah; Muthoharoh; Nur Aisyah; Eko Nursalim; Nanik Sri rahayu (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
This study aims to determine the values of Islamic education in the book of Bidayatul Hidayah and how it is applied in the Integrated Islamic School 2 Daarussalam Sangatta Utara. Applying qualitative methods with a descriptive approach. The result of this research is that Bidayatul Hidayah teaches that obedience to Allah through good deeds and worship is a way to get closer to Him. Acts of courtesy in daily life are practical means to achieve this. In addition, moral values also emphasize the importance of avoiding sin by guarding the limbs and heart from actions that violate religious norms. In the context of relationships, the Book teaches that man's relationship with God is an inseparable aspect of human relationships. Moral education at SDIT 2 Darussalam uses this book as an advanced reference after the BPI module. Discipline, cooperation, and concern for others characterize students at the school. Challenges in its implementation are changes in the social environment, technology, and culture, thus requiring learning strategies that can maintain the relevance of moral values. Collaboration with parents is also a focus to ensure the values are applied consistently in the educational and home environment. Thus, the application of moral values at SDIT Dua Darussalam makes a significant contribution in shaping students' character holistically.